علاقة دافعیة التعلم بالفاعلیة الذاتیة الأكادیمیة لدى عسیري الحساب - عبد اللاوي, سناء (جامعة الوادي university of Eloued, 2016)
ملخص الدراسة: تهدف الدراسة الحالیة للكشف على مستوى الدافعیة للتعلم ومستوى الفاعلیة الذاتیة الأكادیمیة والتعرف على العلاقة بینهم لدى تلامیذ السنة الرابعة ابتدائي عسیري الحساب والتعرف على أثر عامل الجنس على مستویات الدافعیة للتعلم والفاعلیة الذاتیة الأكادیمیة. تم إجراء الدراسة على عینة قوامها ) (88فردا، منهم ) (35تلمیذا و)(53تلمیذة، تم اختیارهم بطریقة المسح الشامل من مجموعة من مدارس ولایة الوادي وسط. حیث تم تطبیق أدوات القیاس المتمثلة في اختبار تحصیلي لاختیار عینة الدراسة ومقیاس الدافعیة للتعلم ومقیاس الفاعلیة الذاتیة الأكادیمیة، وذلك بإتباع المنهج الوصفي. وباستخدام المتوسط الحسابي والتكرارات ومعامل ارتباط بیرسون واختبار "ت" تم التوصل إلى النتائج التالیة: - مستوى الدافعیة للتعلم لدى تلامیذ السنة الرابعة ابتدائي عسیري الحساب مرتفع. - مستوى الدافعیة للتعلم لدى تلامیذ السنة الرابعة ابتدائي عسیري الحساب مرتفع. - توجد علاقة بین الدافعیة للتعلم والفاعلیة الذاتیة الأكادیمیة لدى تلامیذ السنة الرابعة ابتدائي عسیري الحساب. - توجد فروق باختلاف الجنس في مستوى الدافعیة للتعلم لدى تلامیذ السنة الرابعة ابتدائي عسیري الحساب لصالح الإناث. - لا توجد فروق باختلاف الجنس في مستوى الفاعلیة الذاتیة الأكادیمیة لدى تلامیذ السنة الرابعة ابتدائي عسیري الحساب.ب Summary of the Study Study aims to detect the level of motivation to learn and the level of self efficacy academy and learn about their relationshiq with the students of the fourth year of brimary school unable account and identift the imbact of sex workers on the motivation to learn and effectiveness on academic levels Was conducted the study samble strength (88) people including 35 boys and 53 lgirls were selected in a manner comprehensive survey of a group if schools .the state and st.hat been applied measurement tools of testing you get to choose the study sample and measure the motivation to learn and measure the effectiveness of self-Academy bry follow descriptive approach average obasthaddam Comptational Itrations And Self-Testing Labs Artbatabersn T Was Reached Following Results The Level Of Motivation To Learn The Tlamivalsnh Fourth Primary Account Asiri High Self Efficacy Among Students Of The Fourth Year The Level Of Primary Account Asirihigh There Is A Relationship Betwee Motivataion Self-Tlamivalsnh Tho Fourth AsiriPrimayaccount - There are no differences in the level of motivation for learning among students of the primary schooling asir account in favoer of femalzs - There are no differences in the level of self-efficacy among students of the fourth year of primary schooling asir account - And thus level of motivation for education can be said that while individuals are directly linked the level of self-efficacy and academic to have
دراسة میدانیة على تلامیذ سنة رابعة إبتدائي
مذكرة ماستر في علوم التربية تخصص علم صعوبات التعلم
Keywords: الدافعية للتعلم، الفعالية الذاتية، صعوبات الحساب; Learning motivation, self-efficacy, numeracy difficulties; Motivation d'apprentissage, auto-efficacité, difficultés de calcul